Tumor-Infiltrating Lymphocyte Therapy and Neoantigens. Issue 2 (March 2017) - Robbins, Paul F.
Abstract : Abstract: The adoptive cell transfer (ACT) of autologous tumor-infiltrating lymphocytes has been shown to be effective at mediating tumor regression in more than half of patients with metastatic melanoma and in mediating long-term complete regression in approximately one fourth of all patients with this cancer. The success of this approach in patients with cholangiocarcinoma and colon cancer supports efforts to expand ACT therapies to treatment of patients bearing a wide array of cancer types. Recent improvements in deep sequencing of the patient cancers, combined with extensive immunological testing of autologous tumor-infiltrating lymphocytes, indicate that T cells targeting epitopes arising from nonsynonymous somatic mutations, termed neoantigens, play important roles in mediating many of the effective cancer immunotherapies seen in response to ACT.